Lingual Short Split: A Bilateral Sagittal Split Osteotomy Technique Modification - Sant'ana, Eduardo; Souza, Denis Pimenta E; Temprano, Astrid Buysse; Shinohara, Elio H. [UNESP]; Faria, Paulo Esteves Pinto (Wolters Kluwer, 2017)
The technique of sagittal split osteotomy of the mandibular ramus is an established technique that has been evolving over the years, with significant improvements regarding stability, better bone contact between the segments, and possibilities of osteosynthesis. However, paresthesia is common in the postoperatory, sometimes permanent, and undesirable fractures in the subcondylar region can occur leading to longer operative time and extraoral scars. The short lingual split technique is an easy technique that simplifies the horizontal osteotomy of the ramus and decreases the risk of undesirable fractures with a neurosensitive recovery of patients in a much shorter time because of minor trauma and nerve manipulation during the execution.
Keywords: Bilateral sagittal split osteotomy; orthognathic surgery